A integração das tecnológicas de informação e comunicação no processo de ensino aprendizagem em química nas escolas públicas de Manaus - Santiago, Eleonora Celli Arenare (2010)
In a time of constant new electronic devices and technological innovations, the simply act of teaching as we knew on the turn of the century has become obsolete. Education cannot afford to fall behind these changes, and teachers and educators need to learn how to modify methodologies and teaching strategies, as well as to apply this new technology and resources. The knowledge and use of these so called 'information and communication technologies (ICT's) are crucial to the development of high quality education. This research paper addresses the challenges that teachers and educators face when trying to implement these ICT's in their lessons as a way to motivate students in chemistry classes. The observations and notes for this research were obtained in thirteen different public schools in a mid western area of the city of Manaus, the capital of Amazonas, in Brazil. The teachers observed were all chemistry teachers and all schools were part of the Secretaria de Estado de Educação do Amazonas - SEDUC (state education office). The results from the questionnaires used during the research were, then, charted and analyzed according the Likert scale. These charts showed that the implementation and use of the ICT's is still insufficient and a challenge. As a result of this research, a specialized course, which will prepare mainly middle and high school chemistry teachers, was created.